Website-Based Boarding Rental Information System Design - Iqbal Ricky Wahyudi; Fahlevi Dwiyana Irsyad; Luthfi Azmi (Universitas Komputer Indonesia, 2023)
Boarding houses or indekos are services that offer rooms or apartments with a certain amount of payment for a certain period of time (usually monthly or annual payments). The purpose of this research is to create a web-based boarding house information application to develop a boarding house rental service business. To support the research, we use the waterfall method, namely needs analysis, system design, implementation, testing, and testing in making boarding applications. The final result of this research is the creation of a web-based information system that can be used for seekers and providers of boarding rooms. This system will attract the interest of boarding house tenants because this system makes it easy for boarding house seekers to get the boarding house specifications as desired. Likewise, boarding house providers will easily offer their rental services so that they can be rented and occupied by boarding house seekers. It can be concluded that this information system helps in finding suitable boarding houses that can be done online and makes it easy for boarding house owners to promote their place to the fullest.